PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI BADAN USAHA MILIK DESA (BUMDES) DI DESA SIDAKARYA DENPASAR - Ni Luh Ayu Purnia Dewi; Sapta Rini Widyawati; Ni Putu Ayu Sintya Saraswati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Village Owned Enterprises (BUMDES) are a unit of economic institutions in the village which are continuously maintained by the local community according to local wisdom.. So that there are often several problems that must be resolved by BUMDES managers. This study aims to analyze the effect of leadership style, organizational culture, organizational commitment on employee performance. The number of samples in this study were 35 people using the saturated sample method. The research was conducted at BUMDES in Sidakarya Village with research objects on leadership style, organizational culture, organizational commitment and employee performance. Data collection was carried out using a 5-point Likert scale questionnaire. Data analysis techniques using multiple linear regression analysis and t test to test the research hypothesis. The results showed that leadership style had a positive and significant effect on employee performance at Badan Usaha Milik Desa at Desa Sidakarya Denpasar, organizational culture had a positive and significant effect on employee performance at Badan Usaha Milik Desa at Desa Sidakarya Denpasar, organizational commitment had a positive and significant effect on employee performance at Badan Usaha Milik Desa at Desa Sidakarya Denpasar.